A new electromagnetic actuation system on an industrial sewing machine with on-line efficiency monitoring - Silva, Luís F. (2004)
This paper briefly reviews the study to evaluate the standard presser foot performance and a new actuation set-up to avoid the bouncing and the lack of fabric control. The compression force and displacement waveforms are also presented and widely discussed, as well as the seam’s quality analysis. A spectral (Fast Fourier Transform and Harmonic Distortion) analysis on the obtained waveforms, as well as an Admissible Displacement Limits (ADL) analysis are also described as important techniques to be used to supervise the presser foot force and to monitor the feeding efficiency. ADL have proved to be a better method. Further research should be undertaken in this area, in order to achieve, in a near future, a closed loop control of the presser foot.